Fixed Points of Asymptotic Pointwise Nonexpansive Mappings in Modular Spaces - Xue Wang; Ying Chen; Rudong Chen (Journal of Applied Mathematics)
Kirk and Xu studied the existence of fixed points of asymptotic pointwise nonexpansive mappings in the Banach space. In this paper, we investigate these kinds of mappings in modular spaces. Moreover, we prove the existence of fixed points of asymptotic pointwise nonexpansive mappings in modular spaces. The results improve and extend the corresponding results of Kirk and Xu (2008) to modular spaces.